2006
DOI: 10.1007/bf03207046
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermic neuroprotection

Abstract: Summary:The possibility that hypothermia during or after resuscitation from asphyxia at birth, or cardiac arrest in adults, might reduce evolving damage has tantalized clinicians for a very long time. It is now known that severe hypoxia-ischemia may not necessarily cause immediate cell death, but can precipitate a complex biochemical cascade leading to the delayed neuronal loss. Clinically and experimentally, the key phases of injury include a latent phase after reperfusion, with initial recovery of cerebral e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 172 publications
0
27
0
1
Order By: Relevance
“…Two hours after release of occlusion, the metabolic and respiratory acidosis had resolved in both groups; 72 h after occlusion partial pressure of CO 2 and HCO 3 − were slightly lower in the 25-min group.…”
Section: Metabolicmentioning
confidence: 83%
See 1 more Smart Citation
“…Two hours after release of occlusion, the metabolic and respiratory acidosis had resolved in both groups; 72 h after occlusion partial pressure of CO 2 and HCO 3 − were slightly lower in the 25-min group.…”
Section: Metabolicmentioning
confidence: 83%
“…In the first 48 h after premature birth abnormal electroencephalogram (EEG) activity, including seizures, is common and is associated with adverse outcome (2). For potential trials of neuroprotection, it is essential to identify infants with a high risk of adverse outcome as early as possible in the first 6 h of life (3). Amplitude-integrated EEG is an easily applied bedside technology that at term can be used to identify high-risk infants after neonatal hypoxia-ischemia (4).…”
mentioning
confidence: 99%
“…1 In part, partial protection is likely related to the formidable clinical difficulties involved in starting hypothermia within the optimal window of opportunity. 5 A recent study found that asphyxiated infants cooled within 3 hours of birth had better motor outcomes than when hypothermia was started between 3 and 6 hours. 6 However, in a controlled trial, hypothermia was only started in 12% of infants within 4 hours of birth.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, hypothermia (HT) is the only intervention that improves neurologic outcome after HI injury showing promise both experimentally in the neonatal rats, pigs, and sheeps (Bona et al, 1998;Ginsberg et al, 1992;Gunn and Thoresen, 2006) and clinically in asphyxiated infants (Eicher et al, 2005;Gluckman et al, 2005;Shankaran et al, 2005) as well as in adults after out-of-hospital cardiac arrest (Bernard and Rosalion, 2008;Polderman, 2008;Zeiner et al, 2000). From the neonatal asphyxia studies, one in six children benefit from this treatment (Gluckman et al, 2005), and there is an urgent need to improve outcomes for affected infants who might be gained by adding other interventions.…”
Section: Introductionmentioning
confidence: 99%